(untitled) (Psychology Travelogs, 2024)
The article examines the phenomenon known as «unloved child syndrome», characterized by a significant lack of parental love, attention, and support. This syndrome often stems from factors such as stress, adult burnout, or indifference, which can lead to emotional difficulties in children. These challenges frequently manifest as anxiety, depression, low self-esteem, and aggressive behaviors. Contributing factors can be both psychological and social. For example, a lack of proper attention, negative evaluations, and criticism can severely damage a child’s self-esteem, weaken relationships with parents, and provoke conflicts within the family. Research on children’s drawings reveals that among children aged 5-9, signs of emotional neglect are often depicted through symbols such as shelters or natural phenomena like rain, representing protection or emotional distance. Emotional estrangement is typically more pronounced in older children (8-9 years) than in younger ones (5-6 years). Survey results indicate that children who receive regular emotional support and physical contact from their parents feel more loved. Conversely, the absence of family traditions and disregard for a child’s opinions can foster feelings of inadequacy and reduce their self-worth. Utilizing I.M. Markivska’s method has uncovered discrepancies between parents’ and adolescents’ perceptions of emotional closeness in parenting. While parents generally view their parenting style as balanced, around 30% of adolescents report feeling a high level of emotional distance. Additionally, 25% of adolescents feel estranged from their parents, and 31% express dissatisfaction with their relationships, indicating significant communication challenges. Effective parenting requires careful attention to a child’s emotional needs, including fostering open communication, providing support, and avoiding behaviors that could lead to feelings of rejection or neglect.